PRODUCTION OF FLAVOR POWDER WITH CYCLODEXTRIN AS A CARRIER - Thuật, Bùi Quang (Vietnam Journal of Science and Technology, 2012)
SUMMARY Microencapsulation technologies using ß-cyclodextrin as carrier for producing orange and ginger flavor in solid form (flavor powder) were investigated. Main parameters, such as concentration of solvent (ethanol in water), ratio of solvent to carrier, ratio of flavor to carrier, ratio of gum to carrier, speed and time of homogenization process, and temperature of spray drying were optimized, leading to encapsulation efficiencies of up to 92.55% and 93.97% for orange and ginger flavor, respectively. The obtained flavor powders can be conveniently used for creating aromas of food and pharmaceutical products.